Dynamic response of single pile induced by the vibration of tunnel boring machine in hard rock strata - Rui Wang; You Wang; Bin Yan; Bosong Ding (Scientific Reports)
Abstract During metro tunnel construction, Tunnel Boring Machine(TBM) often induces surface and nearby pile vibrations. However, these vibrations are often overlooked due to the short-term passage of the cutterhead beneath the foundation structures. In fact, these vibrations had adverse effects on certain sensitivity structures. Therefore, to analyze the dynamic characteristics of environmental vibrations induced by TBM, on-site vibration monitoring and a numerical modeling method coupling Discrete Element Method with Finite Difference Method were employed for the research. The study focused on a metro tunnel segment passing beneath the foundation of an interchange bridge. The results show that the acceleration of the cutterhead vibration reached 2.55 g during tunnel boring machine operation, with the nearest segment to the cutterhead experiencing a maximum vibration displacement 20% of that at the cutterhead. In weathered limestone formations, when the tunnel depth is less than 10 m, peak accelerations of the ground directly above the excavation face exceed 0.05 g, while pier accelerations reach 0.005 g. Due to cutterhead vibrations, the piers above pile foundations experience low-frequency vibrations (< 12 Hz), with four peak segments identified in the frequency domain, and vibration energy primarily concentrated between 7 and 10.6 Hz. Numerical simulation data based on the DEM-FDM coupling method indicates a negative exponential relationship between peak acceleration and frequency of piles, with a linear positive correlation with amplitude. Piles exhibit the highest sensitivity to vibrations below 4 Hz. Sensitivity analysis results indicate that during tunnel construction, nearby piles are most sensitive to the frequency of the vibration source, followed by the amplitude of the vibration source and the spacing between piles and the tunnel.